(untitled) (Modern education and development, 2025)
This article presents modern medical views on the analysis of research on the morphological aspects of alcohol effects on the internal organs of the human body. The analysis of the literature confirms that the changes in the internal organs observed during alcohol intoxication are practically irreversible, as the compensatory capabilities of the body are disrupted.